Incline plyometrics-induced improvement of jumping performance - Kannas, T. M.; Kellis, E.; Amiridis, I. G. (European Journal of Applied Physiology, 2012)
The aim of this study was to examine the effects of incline plyometrics training on muscle activation and architecture during vertical jumping and maximum strength. Twenty male participants were divided in two training groups which followed after a 4 week training program. The incline plyometrics group (n = 10) trained by performing consecutive jumps on an inclined surface (15°) while the plane plyometrics (PP) group (n = 10) performed the same jumps on a plane surface. Both groups trained four times per week and performed 8 sets of 10 jumps in each session. Subjects performed squat jumps, counter movement jumps and drop jumps (DJ) prior to and immediately after the training period, while the electromyographic activity of the medial gastrocnemius (MGAS) and tibialis anterior muscles and the architecture of MGAS were recorded. Maximal isokinetic and isometric strength of the plantar flexors were performed. Analysis of variance showed that only the IP group improved fast DJ height performance by 17.4 and 14.4% (20 and 40 cm, p < 0.05). This was accompanied by a significantly higher MGAS activity during the propulsion phase (24% from 20 cm and 50% from 40 cm, p < 0.05) of the DJ and a longer working fascicle length (5.08%, p < 0.05) compared with the PP group. There were no significant changes in isokinetic and isometric strength of the plantar flexors after training for both groups. The increase of jumping performance, after incline plyometrics should be taken into consideration by coaches, when they apply hopping exercise to improve explosiveness of the plantar flexors.